Medical Service Management Analysis in the Specialist Medical Centre - I Ketut Agus Prasetyo; Rizka Wahyuni; Teofilus Timon Lirungan; Bambang Ariyanto (Hang Tuah Law Journal, 2021)
Healthcare services, as frontline services, have an essential role in creating a healthy society. Indeed, the community will choose qualified health services for treatment. Hence, the services need to improve the existing management to provide the best quality. The regulation concerning medical service standards is under the Republic of Indonesia's Minister of Health No. 1438 of 2011. The type of research in this article is normative research, using a statutory and conceptual approach analyzed and presented descriptively. As a health service provider facility, the specialist medical center must provide standarized services and have good management. The problem is in the service system's poor management. The specialist medical center must provide effective, safe, quality, and non-discriminatory services by prioritizing patients' interests under professional standards, services, and operational procedures to accelerate service and provide service satisfaction.